2018
DOI: 10.1111/1759-7714.12650
|View full text |Cite
|
Sign up to set email alerts
|

Real world study of regimen containing bevacizumab as first‐line therapy in Chinese patients with advanced non‐small cell lung cancer

Abstract: BackgroundLarge scale randomized controlled trials have demonstrated that the use of bevacizumab in addition to chemotherapy in patients with advanced non‐small cell lung cancer (NSCLC) conveys significant survival benefits. We explored the clinical impact of a first‐line regimen containing bevacizumab (B+) versus a non‐bevacizumab regimen (non‐B) in advanced non‐squamous NSCLC (NS‐NSCLC) patients in a real world setting.MethodsThe medical records of patients with advanced NS‐NSCLC who received first‐line ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…However, in a subset analysis of the ECOG4599 study, no additional effects of Bev were demonstrated in patients ≥70 years old, while more toxicities and a higher incidence of TRD were also observed in these patients than in those <70 years old 17 . In contrast, recent evidence has shown that Bev tends to have weak additional effects on the OS and PFS in Non‐Sq NSCLC patients >75 years old 18 and that Bev‐containing regimens have benefits over Non‐Bev regimens in a real‐world study of Non‐Sq NSCLC patients, including elderly patients 19 . Thus, regimens containing Bev might be beneficial for elderly patients with Non‐Sq NSCLC.…”
Section: Discussionmentioning
confidence: 92%
“…However, in a subset analysis of the ECOG4599 study, no additional effects of Bev were demonstrated in patients ≥70 years old, while more toxicities and a higher incidence of TRD were also observed in these patients than in those <70 years old 17 . In contrast, recent evidence has shown that Bev tends to have weak additional effects on the OS and PFS in Non‐Sq NSCLC patients >75 years old 18 and that Bev‐containing regimens have benefits over Non‐Bev regimens in a real‐world study of Non‐Sq NSCLC patients, including elderly patients 19 . Thus, regimens containing Bev might be beneficial for elderly patients with Non‐Sq NSCLC.…”
Section: Discussionmentioning
confidence: 92%
“…Bevacizumab is an anti-vascular endothelial growth factor (VEGF) monoclonal antibody that can degrade the existing tumor vascular system, inhibit the growth of new blood vessels and resist vascular permeability, thus controlling tumor growth (21)(22)(23). Studies have shown that the addition of bevacizumab significantly improves the clinical benefit of advanced nonsquamous NSCLC compared to platinum-based chemotherapy (24)(25)(26). In addition, bevacizumab was also shown to be effective in brain metastases in the BRAIN study (27).…”
Section: Discussionmentioning
confidence: 99%
“…For patients with positive driver gene mutation and lack of opportunity to continue targeted therapy after resistance to molecular targeted drugs, chemotherapy is often used in the second line, and there is no more effective standard second-line chemotherapy scheme, so the efficacy of the second-line treatment scheme needs to be improved urgently [9,10].…”
Section: Discussionmentioning
confidence: 99%